2003
DOI: 10.1577/m02-164
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Walleyes to Live-Release Angling Tournaments

Abstract: This study examines the physiological impacts of live‐release angling tournament practices on walleyes Sander vitreus (formerly Stizostedion vitreum). Blood and white muscle samples were taken from walleyes following the weigh‐in at several live‐release angling tournaments in southern Ontario. The tournament walleyes had significantly elevated plasma cortisol levels in comparison with those of the control walleyes, indicating that tournament practices elicit a significant stress response in the tournament fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Subsequent research has demonstrated that the effects of individual, sublethal stressors applied in a relatively brief period of time are cumulative (Barton et al 1986; Barton and Schreck 1987;Wedemeyer et al 1990). Walleyes captured in live-release tournaments exhibit changes in physiological parameters associated with elevated activity and cell damage, all of which are indicative of stress (Killen et al 2003(Killen et al , 2006. Barton and Zitzow (1995) found that concentrations of the stress hormone cortisol in juvenile walleyes increased quickly after handling and declined after 3, 6, and 12 h in confinement, but then increased after 24 h. Collectively, this information lends further support to the cumulative-stress hypothesis accounting for posttournament mortality.…”
Section: Discussionmentioning
confidence: 65%
“…Subsequent research has demonstrated that the effects of individual, sublethal stressors applied in a relatively brief period of time are cumulative (Barton et al 1986; Barton and Schreck 1987;Wedemeyer et al 1990). Walleyes captured in live-release tournaments exhibit changes in physiological parameters associated with elevated activity and cell damage, all of which are indicative of stress (Killen et al 2003(Killen et al , 2006. Barton and Zitzow (1995) found that concentrations of the stress hormone cortisol in juvenile walleyes increased quickly after handling and declined after 3, 6, and 12 h in confinement, but then increased after 24 h. Collectively, this information lends further support to the cumulative-stress hypothesis accounting for posttournament mortality.…”
Section: Discussionmentioning
confidence: 65%
“…We suggest that holding walleye in static cages, where walleye have been observed to exhibit sedentary behavior (Goeman 1991), may increase recovery time and, possibly, mortality. Tournament walleyes have shown elevated postcatch stress levels (e.g., increased plasma cortisol, decreased white muscle energy stores; Killen et al 2003). Most studies examining delayed mortality of walleyes (including our study) collected fish after the stressful period extending from catch through weigh-in.…”
Section: Discussionmentioning
confidence: 92%
“…The physiological stress response induced by gillnet entanglement may be exacerbated by injuries incurred while in the net. The significant increases in plasma LDH and CPK seen in gillnet-entangled turtles are indicative of muscle or tissue damage, as these enzymes may leak from ruptured cells into the blood stream (Aguirre et al 1995, Killen et al 2003, Morrissey et al 2005. Several of the studied turtles incurred soft tissue damage from the nets, as documented during the physical examination, and possible cardiac muscle damage due to struggling and overexertion.…”
Section: Discussionmentioning
confidence: 96%